Efficiency of ethanol conversion induced by controlled modification of pore structure and acidic properties of alumina catalysts - Martins, Leandro [UNESP]; Cardoso, Dilson; Hammer, Peter [UNESP]; Garetto, Teresita; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP] (Elsevier B.V., 2011)
Bimodal porous alumina catalysts with both continuous macropores and mesopores were prepared using a dual soft template method. The addition of decahydronaphthalene as emulsifier agent successfully contributed to the formation of macropores. The effectiveness of macropore insertion was evaluated in the model reaction of ethanol dehydration at 300 degrees C. Judging from the results obtained by acidity measurements using temperature programmed desorption of ammonia and the performance of these catalysts in the ethanol dehydration, the introduction of macropores in the catalyst structure enhanced the ethanol conversion. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Macroporous materials; Mesoporous materials; Alumina; Emulsion; Ethanol dehydration